Reduction of Cryptosporidium and Giardia by sewage treatment processes - Lim, Yvonne Ai Lian; Wan Hafiz, W.I.; Nissapatorn, V. (2007)
Cryptosporidium and Giardia are two important pathogenic parasites that have caused many waterborne outbreaks which affected hundreds of thousands of people. Contamination from effluent discharged by sewage treatment plants have been implicated in previous waterborne outbreaks of Cryptosporidium and Giardia. This study evaluated the reduction of Cryptospotidium and Giardia (oo)cysts in two sewage treatment plants (STPA and STPB) in Malaysia which employed different treatment processes for a period of a year. Raw sewage influents and treated sewage effluents were concentrated by repeated centrifugation, subjected to sucrose density flotation and concentrated to a minimal volume depending upon the levels of contaminating debris. Cryptosporidium oocysts and Giardia cysts were enumerated using epifluorescence microscopy. The parasite concentrations in raw sewage were 18-8480 of Giardia cysts/litre and 1-80 of Cryptosporidium oocysts/litre. In treated sewage, the concentration of parasites ranged from 1-1462 cysts/litre and 20-80 oocysts/ litre for Giardia and Cryptosporidium respectively. Statistical analysis showed that sewage treatment process which employed extended aeration could reduce the concentration of Cryptosporidium and Giardia (oo)cysts significantly but treatment process which encompasses aerated lagoon could only reduce the concentration of Giardia cysts but not Cryptosporidium oocysts significantly. This phenomenon is of great concern in areas whereby effluent of sewage treatment plants is discharged into the upstream of rivers that are eventually used for abstraction of drinking water. Therefore, it is important that wastewater treatment authorities rethink the relevance of Cryptosporidium and Giardia contamination levels in wastewater and watersheds and to develop countermeasures in wastewater treatment plants. Further epidemiological studies on the occurrence and removal of pathogenic organisms from excreta and sewage are also recommended, in order that the public health risks can be defined and the most cost effective sewage treatment options developed.